A New Fixed Point in Minoan Relative Chronology? The Pottery Assemblage from the Ceramic Workshop at Zominthos and Its Implications for Neopalatial Chronology - Traunmüller, Sebastian (Archäologischer Anzeiger, 2014)
The small number of securely datable pottery deposits on Minoan Crete poses one of the crucial problems of Neopalatial chronology. Zominthos, however, seems to be the exception to that rule. The ceramic assemblage found in the area of the pottery workshop derives from a sealed deposit par excellence and is thus of paramount chronological significance. All, or at least most of the vases under consideration probably belong to the final series of pottery production at Zominthos, which facilitates the exact dating of the destruction of the ›Central Building‹ and may offer a chronologically fixed point for the use of LM I style pottery. The studies on the material raised theoretical questions on how to date pottery in general, and Neopalatial vases in particular, taking into account taphonomic conditions, the character of decorative styles and vessel shapes, and their chronological significance. This article tries to formulate and discuss these questions by establishing a relative date for the destruction of the ›Central Building‹ and underline its chronological significance for Neopalatial Crete.